Evaluation of peripheral vestibular disorder among elderly patients at the tertiary hospital - Onn, Mohammed Amin (2023)
This study aimed to determine the prevalence of vestibular dysfunction in the Malaysian elderly and its association with presbycusis, age and other associated risk factors. A cross-sectional study was undertaken in a tertiary otorhinolaryngology department and the community. Adults aged 60 years and above who attended ORL clinic at Hospital Universiti Sains Malaysia (HUSM) with or without presbycusis were invited to participate. A total number of 135 elderly were recruited in this study. The main outcome measures including Malay Version Vertigo Symptoms Scale, pure tone audiometry and vestibular assessment were obtained using a Video Head Impulse Test (vHIT). The prevalence of vestibular dysfunction with presbycusis in the study population of 135 elderly participants was 46.7 per cent. The median age was 68 years (range, 60–86 years). The findings showed that there was significant association between presbycusis and tinnitus and also between presbycusis and dizziness. However, the results showed that there was no significant association between presbycusis and vHIT (p = .938). The prevalence among nonprebycusis with vestibular dysfunction was 53.3 %, and the findings showed that there was no significant correlation between vestibular dysfunction without presbycusis with tinnitus and vertigo dizziness. In conclusion, vestibular dysfunction is significantly associated with ageing and presbycusis. Further research into the benefits of additional screening for vestibular dysfunction in elderly presbycusis patients is warranted.